Contemporary Issues Relating to International Child Abduction in Contemplation of the Eighth Special Commission into the Operation of the 1980 Hague Child Abduction Convention (2023) - Freeman, Marilyn; Taylor, Nicola (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
To take stock of the 1980 Hague Convention on the Civil Aspects of International Child Abduction in its 43rd year and to highlight several of the key issues discussed on the agenda of the Eighth Special Commission (10-17 October 2023), this Special Issue considers the convention's implementation and operation within and across the current 103 Contracting Parties. It addresses current global debates on important issues in the context of international child abduction, like habitual residence, the child's best interests, international refugee law, domestic violence, and the use of the 'grave risk'/'intolerable situation' exception to return as outlined in Article 13(1)(b) of the 1980 Hague Convention. Additionally, it explores the consideration of the child's perspective and the utilization of the child objection exception to return as outlined in Article 13(2) of the same convention. The interaction of the 1980 Hague Convention with other international conventions (e.g., the UNCRC 1989) and regional frameworks (e.g., the Brussels II-ter Regulation and the ECHR) is also explored. A central feature of this Special Issue is its focus on the need for, and how best, the 1980 Hague Convention can be nurtured to help meet the current operational and global expansion challenges.